A history of psychology in metascientific perspective - Madsen, K. B. (Advances in psychology (Amsterdam, Netherlands) ;, 1988)
Two fields of interest are combined in this volume: the history of science and the theory, or philosophy, of science (metascience). The result is a history of psychology with emphasis placed upon a metascientific analysis of the work of fourteen psychologists from various periods. Each analysis is set in historical context; a period or school is discussed in each chapter, together with a metascientific analysis of some major works from the respective period or school. The author employs a metascientific descriptive system or `systematology' developed during more than 30 years of work on comparative, metascientific studies of about 50 psychological theories. The results of those studies have been published in previous works. These analyses are also used here for verifying T.S. Kuhn's much-debated theory about the `revolutionary' development of sciences. The author revises Kuhn's theory and shows that it can be applied to the history of psychology. Thus, in a Kuhnian sense, psychology may be said to have had two `normal periods' and two `periods of crisis' leading to school formation.